Penerapan Discovery Learning dengan LKS untuk meningkatkan hasil belajar siswa kelas IV SDN 02 Krompeng - Aliyah Aliyah (Action Research Journal, 2021)
The purpose of this study was to determine the improvement of student learning outcomes at SDN 02 Krompeng Talun through the application of Discovery Learning. The type of research that will be conducted is classroom action research. The subjects of this study were the fourth grade students of SDN 02 Krompeng, Talun, Pekalongan Regency , totaling 25 students . The results of the study showed an increase in learning outcomes and student activeness in learning. In sikus I value - average grade of 69.5 p er sentase classical learning completeness 68% and p er sentase overall activity of 71.4%. In the second cycle the average value of the class is 83.4 with a per sentase completeness of classical study 88 % and persentase overall activity of 77.3%. Thus it can be concluded that discovery learning with worksheets can improve student learning outcomes . Therefore, it is suggested that as teachers should be able to apply discovery learning as an alternative to improve learning outcomes in the form of cognitive abilities and increase student activity.